Improved Sensor Fault-Tolerant Control Technique Applied to Three-Phase Induction Motor Drive - Cuong Dinh Tran; Minh Chau Huu Nguyen (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
An improved fault-tolerant control (FTC) method using mathematical functions is applied to the induction motor drive (IMD) against current sensors and speed encoder failures, which occur when the sensor is disconnected or completely damaged. The IMD with two current sensors and an encoder is speed controlled based on the field-oriented control (FOC) technique in regular operation. In this paper, an FTC unit is implemented in the FOC controller to detect and solve the sensor fault to increase the reliability of the speed control process. The measured stator currents and the feedback speed signal are integrated into the diagnosis algorithms to create a sensor fault-tolerant control function. Three diagnosis functions operating in a defined sequence are proposed for determining the health status of current and speed sensors. The FTC function performs isolation and replaces the faulty sensor signals with the proper estimated signals; then, the IMD will operate in the corresponding sensorless mode. Simulations will be performed to verify the accuracy and reliability of the proposed method under various sensor faults.